Divergent approaches to affordable housing supply in a devolved policy system: Scotland and England after 2010. (1st January 2021) - Gibb, Kenneth
ABSTRACT: Within the UK, Scotland and England operate largely devolved housing policy systems (this paper does not discuss Welsh housing policy, even though much of the same analysis can and should examine the relative divergence of policy between Wales and England, and convergence with Scotland – but that would need to be another paper). Since the 2010 advent of fiscal austerity, housing policy has diverged significantly with respect to affordable and social housing supply programmes. Scotland has returned to council house building and retained a significant grant-funded programme aimed at delivering supply targets intended to tackle unmet housing need. In England, in contrast, following the Coalition Government's Affordable Homes Programme, the response has been to greatly diminish social housing programmes and to replace them with less generous 'affordable' supply programmes for ownership and rent. This experience masks fundamentally different policy settings and assumptions about the housing problem in each country. This paper will first set out the context and mechanisms of housing policy prior to the switch to deficit reduction and austerity, before briefly outlining the policy instruments and strategies adopted in both countries, contrasting their impacts and outcomes. Second, it will investigate the relative effectiveness of these policies, drawing on a synthesis of critical policy science and public policy literatures. The final section discusses the findings in a forward-looking way and also reflects on possible lessons from housing policy divergence and the analytical tools deployed in this paper. Highlights Scotland and England deliver housing policy to support those seeking to live in affordable housing under significantly local policy discretion within the devolved UK. Both countries have pursued increasingly divergent approaches to expanding affordable housing supply. This paper contrasts and explores the two approaches, broadly since the economic crisis of 2008. Adopting a framework drawing on the ideas of policy failure and organized around the structure of a realistic evaluation, we find that Scotland's programme with higher grant per unit has delivered more social housing and met more of its underlying housing need than was the case in England, which was more focused on lower subsidy and higher rent 'affordable' housing. There are wider political and contextual reasons that help explain this divergence in outcome and policy but also uncertainty about how affordable supply will develop in the future.